Color stability of chemically activated reline resin after microwave disinfection: A 1-year clinical trial - Ribeiro, Roberta Chuqui [UNESP]; Giampaolo, Eunice Teresinha [UNESP]; Izumida, Fernanda Emiko [UNESP]; Pavarina, Ana Cláudia [UNESP]; Moffa, Eduardo Buozi [UNESP]; Vergani, Carlos Eduardo [UNESP] (My University, 2011)
Purpose: To evaluate the effect of microwave disinfection on the color stability of a hard chairside reline resin after a 1-year service period. Methods: 40 adult patients aged between 30-75 years, who required denture reline treatment, participated in this study. Tokuyama Rebase II was used to reline complete maxillary dentures. The edentulous subjects were randomly divided into two groups (n=20) and dentures were cleansed according to two methods: CG (control group) - brushing with coconut soap and soft toothbrush; DG (disinfection group) - brushing according to previous methods and microwave disinfection once a week for 3 minutes at 650W. Color parameters in L *a *b * were recorded by spectrophotometer immediately after the reline, at 7 and 15 days, 1, 3, 6 and 9 months and 1 year post-placement. Data were analyzed by two-way repeated-measures ANOVA and Tukey tests (α= 0.05). Results: Color alteration values of DG were significantly lower than those of CG (P< 0.05). Color changes observed after 15 days were greater than values obtained at 7 days recall (P< 0.05). All color changes observed for the CG were considered noticeable (between 1.5 and 3.0 NBS). In DG, color change was slight (between 0.5 and 1.5 NBS). There were statistically significant differences between L * values obtained initially and after 3 months, between 15 days and 3 months and between 15 days and 1 year (P< 0.05). No significant differences were observed between group and time for the parameters a * and b *.